CULTURAL ELEMENTS FOUND IN LAURA INGALLS WILDER'S LITTLE HOUSE IN THE BIG WOODS FOR SUPPORTING ENGLISH TEACHING - Giyatmi Giyatmi; Ratih Wijayava; Nunun Tri Widarwati (Masyarakat Linguistik Indonesia Universitas Andalas, 2015)
The research aims at finding the cultural elements in Laura Ingalls Wilder’s Little House in the Big Woods. This is a descriptive qualitative research. Data source of this research is Laura Ingalls Wilder's Little House in the Big Woods. The data of this research are words, phrases, clauses, sentences and conversation with cultural elements found on the data source. Technique for collecting data is documeniation. The data is classified based on the elements of culture. Technique of data analysis consists of data reduction, data display, and data verification. Theory triangulation is used for data validation. The results of the study show that the cultural elements found in Laura Ingalls Wilder’s Little House in the Big Woods are (1) those dealing with the geographical situation such as animals, plants, and season (2) those relating to the tradition such as eating tradition (meal time, food and beverage, and way of cooking), cloth tradition such as types of clothes, medical tradition, hunting tradition, needle work, sugar snow tradition (3) those dealing with religion and folklore (4) those relating to social values such as speaking manner, eating manner, and meeting people manner.